Empowering Leadership: Strengths and Limitations in the Armed Forces - Teixeira , João; Pais, Leonor; Santos , Nuno (Conferência - Investigação e Intervenção em Recursos Humanos, 2023)
. Since the 19th century, there have been studies on and approaches to leadership effectiveness. These were initially centered on personality attributes, and later, on behavioral characteristics. This was followed by contingency theories and virtuous models, centered either on the leader-subordinate relationship or on the relationship with stakeholders. Having developmental functions, virtuous models can be linked to values that can be considered empowering. Empowering leadership is a process of social and organizational influence for the pursuit of validated objectives (shared or accepted as valid), with five dimensions: 1) Leading by example, 2) Making participatory decisions, 3) Guiding, 4) Informing, and 5) Showing concern (Mônico, Salvador, dos Santos, Pais & Semedo, 2019; Arnold, Turner, Barling, Kelloway & Mckee, 2007). In the late 1980s, the Army War College introduced the term VUCA (Volatility, Uncertainty, Complexity, and Ambiguity). Evolutions have taken place, both for VUCA 2.0 (Vision, Understanding, Clarity, and Agility) (Yoder-Wiser, 2021) and for BANI (Brittle, Anxiety, Non-Linearity and Incomprehensible) (Godoy, 2021), however, the purpose remains the same, namely, putting “order” into “chaos.” Considering the current “post-pandemic” context, where the need for action by the Armed Forces and cooperation with civilian organizations have been demonstrated, there is still a context of generalized scarcity of resources increasing the pertinence of managing and optimizing resources. Since “in every difficulty, there is an opportunity” (Wheeler, 1979), actual context may facilitate changes in an organization with specific characteristics, as is the case for the military. The organization is cautious and slow to incorporate lessons learned, either because of its bureaucratic nature or because of the discomfort in changing an existing and successful approach, despite the intention of transforming the context of an operation (chaotic and lethal) into one where is possible to operate (Hasselbladh, Ydén, 2020). However, these arguments cannot be used as a justification for involution, considering that the military organization fits into the “single loop” and “double loop” learning typology. The first occurs when the error is detected and corrected, as failure to do so will have serious consequences; the second occurs when corrections are made after observation, acting on deeper values, norms, or practices. These two typologies are not mutually exclusive, as they complement each other, with the “single loop” being widespread in the military (easily verifiable in aeronautics), and the “double loop” could fall into inertia due to its complexity, unless actions are consciously done (Soeters, 2022). Empowerment can be conceptualized in structural or psychological terms. The first approach focuses on processes of informal sharing of power, information, and access, and control of resources and rewards (and on the leaders who use them). The second approach focuses on how subordinates/collaborators experience their work and, if positive, on the four cognitions: meaning, competence, self-determination, and impact (Coun, Peters, Blomme, Schaveling, 2021). Empowering Leadership can be seen through two theoretical lenses: structural empowerment and the motivational perspective, with the first focusing on sharing power and delegating the leader's tasks and the second focusing on the subordinate's perception of their empowerment and respective work motivation (Hieu, 2020). Both are relevant to the military context; their specificity, values, culture, environment, and the operational product must be considered. For example, responsibility and accountability must be taken into account before delegation as the operational environment is chaotic and lethal. While delegation can be adaptive and efficient in some situations as it brings gains in organizational engagement and belonging, it could also become destructive for the organization in other situations. Motivations may differ depending on the internal and external stakeholders and on the nature of a given mission. However, regardless of the variables, the “partnership” of empowerment must be clear, coordinated, and accepted by all (Khorram-Manesh, Goniewicz, Phattharapornjaroen, Gray, Carlstrom, Sundwall, Sundwall, Hertelendy, Burkle, 2022). In the military context, where agility, dynamism, and digital transformation are permanent, military organizations see an increase in the number of missions and a decrease in the available resources, forcing leadership into a fundamental role. Through the style used, leaders can greatly impact outcomes even in organizations that are “resistant to change.” Organizations that are willing to change will always have something to benefit from chaos (Chis-Manolache, 2021).